Prevalence and Relation of Vitamin D and Obesity among Infertile Women - Ola Mustafa,; Salihah Mustafa, (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. The current study aimed to assess the prevalence of vitamin D deficiency and obesity in infertile women. Methods. A cross sectional prospective study was conducted from Massa hospital, upon 153 infertile women between ages 21-44 years. All patients were assessed by taking a complete history, clinical examination, vitamin D investigation, and BMI measurement. Vitamin D categorize used were as the following; mild vitamin D deficiency - serum 25(OH)D levels 12-19 ng/mL (30-49 nmol/L), moderate vitamin D deficiency - serum 25 (OH)D 5-11 ng/mL (12.5-29 nmol/L), and severe vitamin D deficiency - serum 25(OH)D level < 5 ng/mL (< 12.5 nmol/L). Results. The present study did not detect a significant difference in the mean serum vitamin D of the infertile women (p value=0.605). The results also showed an indirect effect for factors resulting from interactions among them. The interactions of BMI and infertility (p value=0.040*), vitamin D and infertility (p value=0.047*), vitamin D and BMI (p value=0.044*) and age and infertility (p value=0.022*) were significant and illustrated pure effects on trial results and gynecological disease types. Otherwise, the study demonstrated a negative linear association between vitamin D levels and obesity in infertile women. Conclusion. Our findings suggested that a decreased vitamin D might correspond to a higher prevalence of obesity in infertile women, which reminded us to pay more attention to the supplement of vitamin D in obese infertile women.